2020
DOI: 10.1108/apjba-05-2020-0160
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of oversubscription of SME IPOs in India: evidence from quantile regression

Abstract: PurposeThe study aims to measure the subscription level and examine the determinants of oversubscription of small and medium enterprise (SME) initial public offerings (IPOs) in India.Design/methodology/approachThe study employs cross sectional data to analyze 403 SME IPOs issued from Feb 2012 to May 2018 and listed on Bombay Stock Exchange's small and medium enterprise (BSE SME) platform and National Stock Exchange (NSE) EMERGE to investigate the determinants of oversubscription of SME IPOs. Hence, the study m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 68 publications
1
14
1
1
Order By: Relevance
“…According to signal theory, larger issue sizes send good quality signals to investors thereby increasing their demand. Meanwhile, a smaller issue size is a bad signal for risk-neutral investors and will lead to a lower probability of oversubscription (Arora and Singh, 2020b). This is supported by the results of several other studies conducted by (Albada et al, 2019), (Mehmood et al, 2020), (Tajuddin et al, 2015) which proves a negative relationship between supply size and oversubscription.…”
Section: Theoretical Reviewmentioning
confidence: 52%
See 1 more Smart Citation
“…According to signal theory, larger issue sizes send good quality signals to investors thereby increasing their demand. Meanwhile, a smaller issue size is a bad signal for risk-neutral investors and will lead to a lower probability of oversubscription (Arora and Singh, 2020b). This is supported by the results of several other studies conducted by (Albada et al, 2019), (Mehmood et al, 2020), (Tajuddin et al, 2015) which proves a negative relationship between supply size and oversubscription.…”
Section: Theoretical Reviewmentioning
confidence: 52%
“…Larger company size encourages higher investor demand which results in a higher possibility of oversubscription events for a stock (Badru and Ahmad-Zaluki, 2018). Firms with a larger asset base have reduced information asymmetry and uncertainty related to future stock values (Arora and Singh, 2020b). Therefore, investors' bids for bids tend to be higher for firms with larger asset bases compared to firms with smaller asset bases.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…This study uses a quantitative approach to establish relationships between independent variables viz., issue price, issue size, firm size, listing delay, and underpricing, and IPO oversubscription. Based on the works of Arora & Singh (2020) and Low & Yong (2011) The dependent variable used in this study is the oversubscription ratio. This ratio shows how many times an issue is subscribed to by the investors.…”
Section: Methodology 31 Research Methodsmentioning
confidence: 99%
“…In the literature, factors that cause the oversubscription in the IPOs have received substantial attention (Avci, 2021;Dong et al, 2021;Gupta, Singh, & Yadav, 2022;Hoque & Mu, 2021;Payne, Trudell, Moore, Petrenko, & Hayes, 2022). These include investor demand (Arora & Singh, 2020;Mensi, Lee, Vinh Vo, & Yoon, 2021); promotional activities (Arora & Singh, 2020;Lan & Khoi Thach, 2022); previous number of IPO's conducted in the country (Lan & Khoi Thach, 2022;Mehmood, Mohd-Rashid, Ong, & Abbas, 2021); prior information about the company making the IPO (Chowdhry & Sherman, 1996;Hayat & Hassan, 2017), level of market efficiency (Avci, 2021;Karnatak, Malik, & Udayan Karnatak, 2021;Mehmood et al, 2021); role of the regulator (Arora & Singh, 2020;Dong et al, 2021); market capitalization (Arora & Singh, 2020;Lan & Khoi Thach, 2022); economic performance of the country (Arora & Singh, 2020;Mehmood et al, 2021); monetary policies of the country (Adra, 2021;Arora & Singh, 2020;Tekatli, 2021); investor perception about the IPO and the market (Gupta et al, 2022;Lan & Khoi Thach, 2022;Mehmood et al, 2021) and performance of previous IPOs of the company, its peers and other companies amongst the others (Agarwal, Liu, & Rhee, 2008;Badru & Ahmad-Zaluki, 2018;Lan & Khoi Thach, 2022;Tajuddin, Mohd-Rashid,...…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Moreover, the current study reports an average investor demand of 25.15 times, which is significantly lower than the findings of other studies such as Low and Yong (2011) and Albada et al (2019), where the authors reported an average investor demand of 33.59 times and 36.62 times, respectively. Furthermore, Malaysia has a relatively higher average subscription level as compared to other emerging economies like Bangladesh of 20.20 times (Rahman et al, 2017), Pakistan of 2.52 times (Mehmood and Mohd-Rashid, 2020) and India of 10.28 (Arora and Singh, 2020). In accordance with Chowdhry and Sherman's (1996) model, fixed-price regime issues are characterised by extreme OSRs in comparison to book-building issues, which is attributable to the high level of uncertainty.…”
Section: Descriptive Statisticsmentioning
confidence: 99%